ANALISIS RASIO AKTIVITAS DAN PROFITABILITAS PADA CV MEGA MARSAILO DITANJUNG REDEB (AKUNTIA JURNAL Jurnal Akuntansi, Terpercaya, Menginspirasi dan Asli, 2019)
Analysis of Activity and Profitability Ratios at CV Mega Marsailo at Tanjung Redeb Berau.The purpose of writing this thesis is to find out more clearly about the financial performance of CV Mega Marsailo in Tanjung Redeb from 2015 to 2017. The analytical tool used is the calculation of the ratio of activity and profitability. Based on the results of the study there was no increase in the ratio of assets and profitability in 2015-2017, the hypothesis was rejected. Suggestions companies must be able to increase sales on a large scale with the aim to increase the amount of revenue that has an effect on increasing company profits. Calculation of activity and profitability ratios using total assets turnover (2015 = 4.93 times, 2016 = 12.23 times, 2017 = 10.03 times), accounts receivable turnover (2015 = 0 times, 2016 = 0 times, 2017 = 273, 03 times), Net Profit Margin (2015 = 15.65%, 2016 = 70.5%, 2017 = 3.67%), Return On Investment (2015 = 77.19%, 2016 = 86.28%, 2017 = 36.84%), and Return On Equety (2015 = 71.33%, 2016 = 81.18%, 2017 = 36.28%).